Renal function and outcome of patients with non-valvular atrial fibrillation. Issue 10 (30th August 2021) - Barashi, Rami; Hornik-Lurie, Tzipi; Gabay, Hagit; Haskiah, Feras; Minha, Saar; Shuvy, Mony; Assali, Abid; Pereg, David
Abstract: Aims: Atrial fibrillation and renal dysfunction are associated with increased cardiovascular risk. We examined the association between renal function and incident ischaemic stroke or myocardial infarction in patients with atrial fibrillation treated with direct oral anticoagulants (DOACs). Methods and results: This study was conducted using a large health record database. Included were 19 713 patients with first time diagnosis of non-valvular atrial fibrillation treated with DOACs between 2010 and 2018. Patients were categorized into four groups according to the estimated glomerular filtration rate (eGFR) (<30, 30–59, 60–89, and ≥90 mL/min/1.73 m 2 ). Ischaemic stroke and acute myocardial infarction rates were compared between the groups. During 55 086 person-years of follow-up, there were 2295 (11.6%) cases of ischaemic stroke and 1158 (5.9%) cases of acute myocardial infarction. There was a significant inverse association between eGFR and the risk of myocardial infarction. A multivariate analysis using the group with eGFR ≥90 mL/min/1.73 m 2 as a reference demonstrated an increased risk of myocardial infarction with lower eGFR [hazard ratio (HR) = 1.2 95% confidence interval (CI) 0.9–1.4, HR = 1.4, 95% CI 1.2–1.7, and HR = 2.5, 95% CI 1.8–3.4 for patients with eGFR 60–89, 30–59, and <30 mL/min/1.73 m 2, respectively, P < 0.001]. Each 10 mL decrease in eGFR was associated with an 8% increase in the risk of myocardial infarction. There was no association between eGFR and the risk of ischaemic stroke (HR = 0.9 95% CI 0.8–1.1, HR = 0.93, 95% CI 0.8–1.1, and HR = 1.1, 95% CI 0.8–1.4 for patients with eGFR 60–89, 30–59, and <30 mL/min/1.73 m 2, respectively, P = 0.325). Conclusions: Renal dysfunction is associated with an increased risk of myocardial infarction but not of ischaemic stroke among patients with atrial fibrillation treated with DOACs. Graphical Abstract: